Total Quality Management in Media Outfits and Organizational Performance - Nwokeocha, Ifeanyi (MultiTech Publisher, 2024)
Total Quality Management (TQM) is a comprehensive management philosophy adopted by organizations to continuously enhance the quality of processes, products, and services. Its core objective is to meet or exceed customer expectations, thereby improving customer satisfaction and overall organizational performance. TQM has emerged as an essential practice in modern business environments due to its proven effectiveness in enhancing performance metrics. This study investigates the implementation of TQM in media organizations and its impact on organizational performance. Findings suggest that TQM underscores the significance of human resources in achieving quality excellence. Effective human resources management aligned with quality management principles is crucial for achieving total quality. Failures and costs often stem from communication gaps and lack of awareness. When quality becomes a shared priority across the organization, it becomes feasible to deliver products that meet customer requirements and preferences while minimizing defects in products and services.